The Growth of Education Revenues from 1998-2006: An Update on What Accounts for Differences among States and the District of Columbia in the Context of Adequacy - Nicola Alexander (Educational Considerations, 2012)
This article is an update of a previous study by the author which examined the growth of elementary and public school revenues for school years 1982-1983 through 1991-1992.
Keywords: federal sources; elementary and public school; revenues; enrollment; convergence; 50 states; income; per-pupil revenues; variables; adequacy; District of Columbia